Socialization of the Sumber Sejahtera Credit Union Cooperative on Jl. Bandarmasih DPR Complex Gg. V Banjarmasin City - Isra Ul Huda; Melania Melania; Adista Anjar Diany (Mandalika Journal of Community Services, 2025)
This report presents the results of community service carried out by the community service team from the Banjarmasin Pancasetia College of Economics on September 7, 2024, which aims to socialize the Sumber Sejahtera Credit Union cooperative at the DPR Gg. V Complex, Banjarmasin City. This activity aims to increase public understanding of the importance of cooperatives in supporting economic empowerment and introducing financial products offered by cooperatives. This socialization also emphasizes the importance of financial literacy as a tool for wise and effective financial management. In this activity, the material presented covered various aspects, ranging from the definition of cooperatives, its benefits for members, to financial products that can be used by the community, such as savings, loans, and microinsurance. In addition, participants were also invited to understand the basic concept of sustainable personal and family financial management. This activity involves various elements of society, including members of the cooperative and the surrounding community, to increase awareness and participation in cooperatives. The evaluation conducted after the socialization showed that the public's understanding of cooperatives and financial management increased significantly. The results of this activity are expected to make a positive contribution to improving the quality of life of the community through cooperatives, as well as encouraging financial inclusion and more equitable economic empowerment among the community